IMPLEMENTASI PROGRAM KAMIS BERBAHASA BANJAR DI SD MULTIKULTURAL - Fauzan, Muhammad; Suriansyah, Ahmad; Budi Harsono, Arta Mulya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Banjar language is the everyday language used by the people of South Kalimantan, especially in Banjarmasin. The use of Banjar language is also inseparable from all levels of education, one of which is in elementary schools. This study aims to explore the implementation of the Kamis Berahasa Banjar (KAMBAR) program at SDN Kebun Bunga 5. This study uses a qualitative approach with a case study design. The research sample includes 1 principal, 1 fifth-grade teacher, and 1 second- and third-grade student each, in addition to all students being indirectly involved in the data collection process through field observations. The results of the analysis show an increase in teachers' and students' insight into the Banjar language. The KAMBAR program has a positive impact at SDN Kebun Bunga 5. This activity can increase teachers' and students' insight into the Banjar language and culture.